Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Kebijakan Deviden, Kebijakan Hutang dan Kebijakan Investasi Terhadap Nilai Perusahaan Pada Sektor Manufaktur Di Bursa Efek Indonesia Periode 2011-2014 - Afiantoro, Teguh, Dr. Fatchan Achyani, S.E, M.Si (2016)
This study aimed to analyze the relationship between managerial ownership, institutional ownership, dividend policy, debt policy and investment policy on firm value. The study involved 18 companies listed in the Indonesia Stock Exchange with a period of 4 years of research conducted during the year 2011 up to 2014. The research sample was determined by purposive sampling method. Testing the hypothesis in this study using multiple linear regression analysis. The results of the study on the regression model is known, as follows: Variable managerial ownership and investment policies have a significant effect on firm value. While variable institutional ownership, dividend policy and debt policy has no significant effect on firm value.